2015
DOI: 10.1002/alr.21499
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐assisted staging of chronic rhinosinusitis correlates with symptoms

Abstract: Objectives The Lund-Mackay (LM) staging system for Chronic Rhinosinusitis (CRS) does not correlate with clinical parameters, likely due to its coarse scale. We developed a “Modified Lund Mackay” (MLM) system, which uses a 3D, computerized method to quantify the volume of mucosal inflammation in the sinuses, and sought to determine whether the MLM would correlate with symptoms and disease-specific quality of life. Methods We obtained Total Nasal Symptom Score (TNSS) and Sinonasal Outcomes Test (SNOT-22) data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 32 publications
3
36
1
1
Order By: Relevance
“…Whereas preoperatively a majority of patients was categorised in class of severity IV (severe to highly severe symptoms) or III (moderate to severe symptoms), five to seven months after functional endoscopic sinus surgery (FESS) most patients improved to class I (no or mild symptoms) or class II (mild to moderate symptoms) most of the patients indicating good regeneration of the ostiometal complex after FESS. A positive correlation only between PNS and volume of the maxillary sinuses was observed, and this result is corroborated by another study 8 . In another study, the volumetric scoring system showed a higher correlation with improvement in scores for symptoms, endoscopic exam and quality of life as non-volumetric-based CT scores 10 .…”
Section: Comparison With Other Studiessupporting
confidence: 81%
See 2 more Smart Citations
“…Whereas preoperatively a majority of patients was categorised in class of severity IV (severe to highly severe symptoms) or III (moderate to severe symptoms), five to seven months after functional endoscopic sinus surgery (FESS) most patients improved to class I (no or mild symptoms) or class II (mild to moderate symptoms) most of the patients indicating good regeneration of the ostiometal complex after FESS. A positive correlation only between PNS and volume of the maxillary sinuses was observed, and this result is corroborated by another study 8 . In another study, the volumetric scoring system showed a higher correlation with improvement in scores for symptoms, endoscopic exam and quality of life as non-volumetric-based CT scores 10 .…”
Section: Comparison With Other Studiessupporting
confidence: 81%
“…In our study, postoperative scarring or adhesion formation at the ostium was not observed in most of the patients indicating good regeneration of the ostiometal complex after FESS. A positive correlation only between PNS and volume of the maxillary sinuses was observed, and this result is corroborated by another study. In another study, the volumetric scoring system showed a higher correlation with improvement in scores for symptoms, endoscopic exam and quality of life as non‐volumetric‐based CT scores.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…All patients getting sinus scans had rhinologic complaints (such as congestions or post nasal drip), including 2 patients undergoing evaluation prior to stem cell transplantation. The first period represented subjects who were analyzed in our initial study 9 and who further met the LM ≥ 4 criterion (n=23). The second period added new subjects for the present study (n=22).…”
Section: Methodsmentioning
confidence: 99%
“…9 The Chicago modified Lund-Mackay (Chicago MLM) scoring system (previously referred to as “modified Lund-Mackay system” 9 ) uses specialized software to calculate the mucosa-to-sinus volume ratio through three-dimensional analysis of axial CT images. Unlike the LM system, the Chicago MLM system provides a quantitative and objective method to measure differing degrees of mucosal inflammation on a continuous scale from 0 to 1 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%